2014
DOI: 10.1111/desc.12192
|View full text |Cite
|
Sign up to set email alerts
|

Reducing an in‐group bias in preschool children: the impact of moral behavior

Abstract: How impressionable are in-group biases in early childhood? Previous research shows that young children display robust preferences for members of their own social group, but also condemn those who harm others. The current study investigates children's evaluations of agents when their group membership and moral behavior conflict. After being assigned to a minimal group, 4- to 5-year-old children either saw their in-group member behave antisocially, an out-group member act prosocially, or control agents, for whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
73
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 56 publications
11
73
1
2
Order By: Relevance
“…As mentioned previously, children's group biases are malleable and capable of attenuation when presented with bias-incongruent social or moral information (Hetherington et al, 2014;Wilks & Nielsen, 2017). That bias attenuation was associated with this LPP effect, but not P2 or N2, is consistent with a deliberate evaluation account of attitude change rather than an implicit, evaluative conditioning one.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…As mentioned previously, children's group biases are malleable and capable of attenuation when presented with bias-incongruent social or moral information (Hetherington et al, 2014;Wilks & Nielsen, 2017). That bias attenuation was associated with this LPP effect, but not P2 or N2, is consistent with a deliberate evaluation account of attitude change rather than an implicit, evaluative conditioning one.…”
Section: Discussionsupporting
confidence: 73%
“…The first was to identify the mechanism underlying bias attenuation in response to observing "bias-incongruent" moral acts (in-group harmful actions and outgroup helpful actions) with greater frequency than expected, "biascongruent" ones (in-group help and out-group harm) (Hetherington et al, 2014;Wilks & Nielsen, 2017). The first was to identify the mechanism underlying bias attenuation in response to observing "bias-incongruent" moral acts (in-group harmful actions and outgroup helpful actions) with greater frequency than expected, "biascongruent" ones (in-group help and out-group harm) (Hetherington et al, 2014;Wilks & Nielsen, 2017).…”
Section: Research Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macdonald, Schug, Chase, and Barth (2013) showed that 4-year-olds did not preferentially endorse the labels provided by a previously reliable out-group member over those of an unreliable in-group member, even though group membership was randomly assigned and bore no social significance. Hetherington, Hendrickson, and Koenig (2014) explored the specific influences of group membership and moral behavior on children's social preferences and learning decisions. They assigned 4-and 5-year-old children to arbitrary groups and found that preschoolers' preferences for and willingness to share with an in-group member were substantially reduced when she behaved antisocially, but they still preferred to learn from the antisocial in-group member as opposed to a neutral out-group member.…”
Section: Moral Warmthmentioning
confidence: 99%
“…This research has documented that children (as early as preschool age) affiliate with groups and begin to exhibit ingroup preferences and, at times, outgroup negativity in both authentic and minimal group contexts (Aboud, 1988;Dunham, Baron, & Carey, 2011;Kinzler & Spelke, 2011). Much of the research investigating this intersection has focused narrowly on the moral domain in intergroup contexts (Hetherington, Hendrickson, & Koenig, 2014;Rhodes & Chalik, 2013), without also considering the conventional domain (Smetana, Jambon, & Ball, 2014;Turiel, 1983). Much of the research investigating this intersection has focused narrowly on the moral domain in intergroup contexts (Hetherington, Hendrickson, & Koenig, 2014;Rhodes & Chalik, 2013), without also considering the conventional domain (Smetana, Jambon, & Ball, 2014;Turiel, 1983).…”
mentioning
confidence: 99%